Optimization of Gel Formulation and Antibacterial Activity against Cutibacterium acnes from Combined Extracts of Caesalpinia sappan and Carthamus tinctorius Using Simplex Lattice Design - Azizah, Umi Hani; Ika Yuni Astuti; Aktsar Roskiana (Universitas Muhammadiyah Surakarta, 2025)
Acne vulgaris remains a common dermatological disorder in which Cutibacterium acnes plays a central role, while concerns over antibiotic resistance highlight the need for safe natural alternatives. This study aimed to develop and optimize a topical gel formulation containing combined extracts of Caesalpinia sappan and Carthamus tinctorius with antibacterial activity against C. acnes. An experimental design was employed using the Simplex Lattice Design (SLD) method to optimize the proportions of Carbopol 940 and triethanolamine as gelling and stabilizing agents. The prepared gels were evaluated for physical characteristics, stability, hedonic properties, and antibacterial activity using the agar diffusion method. The optimized formulation, with a desirability value of 0.931, demonstrated appropriate viscosity, spreadability, and pH within the physiological range. Stability testing through six freeze–thaw cycles confirmed no significant changes in organoleptic or physicochemical parameters. Hedonic evaluation indicated good acceptance regarding odor, texture, and non-irritating properties, though color preference was slightly lower. Antibacterial assays showed that both the optimized gel and combined extracts produced strong inhibition zones against C. acnes, comparable to clindamycin as a positive control. These findings confirm that the combination of C. sappan and C. tinctorius extracts, when optimized through statistical design, can yield a stable and effective herbal gel with strong antibacterial activity. This research highlights the potential of integrating traditional medicinal plants with modern formulation approaches to develop safe, natural, and sustainable alternatives for acne management.